Online Teaching in Writing by Means of Slack Application - Yusep Heryandi; Ishak Said; Rina Herlina (Journal of English Education and Teaching, 2020)
This study deals with online teaching by using ICT in teaching writing skill. This study aimed in investigating the activity of the teacher, the teacher’s perception, and students’ perception to the process of teaching online by means of slack application in students writing skill. A qualitative design with a case study approach was employed in this study by conducting classroom observations and interviews to collect the data regarding the use and the impact of slack application in teaching writing by the teachers in EFL classrooms. The participant of this study were the students at one of senior high school in Tasikmalaya. In analyzing the data, multiple sources of data collection commonly known as triangulation as purposed was employed. The findings showed that the teacher used four steps in optimizing slack application in an online teaching writing. Introducing, memorizing and giving feedback were the strategy in teaching online by using slack application in classroom. This study suggested that English teacher need to apply Online Application as a system and tools to support the teacher in how they give a task, planning, and empowering in their teaching practices.